A dog's purpose [videorecording (DVD)] - Robertson, Brittany; Apa, K. J., (Keneti James), 1997-; Ortiz, John; Quaid, Dennis; Cameron, W. Bruce (Universal Pictures Home Entertainment, 2017)
It shares the soulful and surprising story of one devoted dog who finds the meaning of his own existence through the lives of the humans he teaches to laugh and love.